The rise and decline of industrial foundations as controlling owners of Swedish listed firms: the role of tax incentives. Issue 2 (3rd May 2020) - Henrekson, Magnus; Johansson, Dan; Stenkula, Mikael
ABSTRACT: Beginning in the interwar period, industrial foundations became a vehicle for corporate control of large listed firms in Sweden. In the 1990s they were replaced by wealthy individuals who either directly own controlling blocks or who own them through holding companies. We study potential explanations for this change and propose two tax-related candidates: shifts in the relative effective taxation across owner types and the dismantling of inheritance taxation that prevented the generational transfer of the ownership of large controlling blocks. We exploit newly computed marginal effective capital income tax rates across capital owners, accounting for all relevant factors, including rules governing tax exemptions. We show that the 1990–91 tax reform, abolition of the wealth tax for controlling owners in 1997, 2003 tax exemption of dividends and capital gains on listed stock for holding companies with a voting or equity share of at least 10 percent, and abolition of the inheritance and gift taxes in 2004 reversed the rules of the game. Recently, control has largely been wielded through direct ownership, and the role of foundations is rapidly declining. These findings point to the importance of tax incentives for the use of foundations as the control vehicle of listed firms.